Coronary syndromes associated with COVID-19: A literature review - Siqueira, Maria Clara Teixeira; Silva, Mariana Alves Gama Souza da; Nogueira, Carolina Teixeira; Matos, Maria de Lourdes Ferreira Medeiros de; Matos, Alcemar Antônio Lopes de; Santos, Fernando Basílio dos (Seven Editora, 2024)
In January 2020, the World Health Organization (WHO) declared a state of Public Health Emergency of International Concern. The rapid population illness and the increase in the number of deaths from unknown causes generated a social panic. In view of this, it was understood that the broad spectrum of symptoms related to the respiratory infection of SARS-CoV-2 has a direct impact on the cardiovascular and immune systems and can cause conditions both in the acute phase of the infection and in a later phase. This study was developed from a meticulous and integrated review of the literature in recent publications, including articles in scientific journals, gathered in search engines dated between the period 2019 and 2021. Pooled data from the Pan American Health Organization, the Ministry of Health, and the World Health Organization were also used. Thus, it aims to highlight the various implications of COVID on the cardiovascular system. It should be remembered that the symptoms of the coronavirus are quite nonspecific and varied, and may include: headache, dry cough, hyperthermia, sore throat, anosmia, hypogeusia, dysgeusia, rash and skin irritation, myalgia, diarrhea, dyspnea and other respiratory discomforts. In view of the immune system and other morbidities, the evolution of the condition can lead to a worse prognosis. In the compilation of reviewed articles, it was observed that myocardial injury caused by SARS-CoV-2 is related to ACE-2, since the virus uses these ACE receptors to enter the cell, and, even understanding this mechanism of action, the use of enzyme blockers that act directly on this factor as a possible form of treatment is still a distant reality. There is no scientific evidence to support the use of these medications in suppressing ACE activity to reduce the viral effect on the body. DOI:https://doi.org/10.56238/sevened2023.007-090